Visibilidad internacional de las revistas españolas de historia medieval - Malalaña Ureña, Antonio (En la España Medieval, 2007)
Spanish journals of history, like publications in other fields, are being submitted to quality evaluations based on very diverse methodological criteria. One of these methodological perspectives attempts to establish the level of international visibility of each journal. This study analyzes a limited group of Spanish journals of medieval history.